2018
DOI: 10.18393/ejss.327900
|View full text |Cite
|
Sign up to set email alerts
|

Microbial communities and their characteristics in a soil amended by nanozeolite and some plant residues: Short time in-situ incubation

Abstract: Article Info Received : 29.04.2017 Accepted : 08.07.2017 Soil microbial communities and their related characteristics are an important agent for soil fertility, productivity, and sustainability. Also, they are useful indicators of soil quality and life index in agricultural systems. The objectives of this study were the effect of nanozeolite and plant residues on soil microbial communities and their characteristics and also, the assessment of incubation timing on soil microbial properties. Soil microorganisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Overall, starting with the same inoculum, the carrier materials (glass beads or zeolite) shaped the attachment and development of different microbial communities. Our results confirmed previous observations with sulfate-reducing bacteria (Basu and Baldwin 2000) or soil communities (Aminiyan et al 2018). The effect of the carrier material was also confirmed by diversity indexes and statistical analysis, showing that such difference was significant (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, starting with the same inoculum, the carrier materials (glass beads or zeolite) shaped the attachment and development of different microbial communities. Our results confirmed previous observations with sulfate-reducing bacteria (Basu and Baldwin 2000) or soil communities (Aminiyan et al 2018). The effect of the carrier material was also confirmed by diversity indexes and statistical analysis, showing that such difference was significant (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…This point can be explained by soil MBC content that contributed substantially to variations in soil CO 2 fluxes among the different litter manipulation treatments (Figure 5a). Generally, the litter layer has been recognized as an important source of soil organic matter and nutrients, which can strongly affect the energy supply and microbial substrate availability [41,42]. Previous studies and meta-analyses have reported that the increase in soil respiration with litter addition is mainly due to the strong positive effects of the litter inputs on soil substrate availability, such as nutrient availability, labile carbon, and the abundance of soil microorganisms [43][44][45].…”
Section: Effects Of Litter Manipulation Treatments On the Soil Co 2 F...mentioning
confidence: 99%
“…Decreased crystal size of nanozeolite is found beneficial which broadens the application of alumino silicates for different purposes (Mintova et al 2016). Application of nanozeolite @ 30% in soil with alfalfa straw enhanced the fungal and bacterial population (Aminiyan et al 2018) and also improved soil health under maize cultivation when applied @ 50 mg L −1 (Khati et al 2018).…”
Section: Introductionmentioning
confidence: 99%